Ethnography of Communication: Woman Role Representation in the Proverb “Bapa’ Babu’ Guru Rato” as Madurese Proverb - Cristian Anggraini (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study discerns the contextualization of the proverb bapa' babu' guru rato (father, mother, teacher, ruler), on women's involvement. Data was collected utilising ethnography of communication framework, including participant observation, triangulation, and in-depth interviews, and analysed using the Miles and Hubermann approach with Nvivo software. The findings show that the proverb emphasises women's responsibilities in education, leadership, and household management for societal betterment. The study suggests that proverbs such as bapa' babu' guru rato (father, mother, teacher, ruler) impact community attitudes and actions, acting as cultural guides that considerably increase women's involvement and social growth.